Preparation method of sealing aging resistant PBAT resin, biodegradable plastic and application

By introducing isophthalic acid into the PBAT resin, the content and regularity of benzene ring are reduced, and combined with pre-polycondensation and final polycondensation reactions, a PBAT resin resistant to sealing aging is prepared, which solves the problem of degradation of sealing performance after moisture and heat aging, and achieves higher sealing performance and aging resistance.

CN119638968AInactive Publication Date: 2025-03-18YINGKOU KANGHUI PETROCHEM

Patent Information

Application Number
CN202411859228.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-03-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

After the existing PBAT resin products are aging in humidity and heat or placed in room temperature for a long time, the sealing performance will decline, resulting in linear tearing at the sealing, which cannot meet the usage requirements.

Method used

The first intermediate product was obtained by performing a first esterification reaction of adipic acid, butylene glycol and the first catalyst; then the second intermediate product was subjected to a second esterification reaction of terephthalic acid, isophthalic acid, butylene glycol and the second catalyst; then the two were subjected to a pre-polycondensation reaction in a polymerization reactor to obtain a pre-polycondensation product, and a final polycondensation reaction was performed to prepare a sealing aging-resistant PBAT resin.

Benefits of technology

The prepared sealing aging-resistant PBAT resin has higher compatibility with other fillers when modified downstream. The edge sealing bags are better sealing and have better aging resistance. The sealing strength is still ≥15N/15mm after 30 days of storage, and the sealing performance loss is less.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005192748950000081
    Figure BDA0005192748950000081
Patent Text Reader

Abstract

The invention provides a preparation method of sealing aging resistant PBAT resin, biodegradable plastic and application, and the preparation method comprises the following steps: mixing adipic acid, butanediol and a first catalyst, and carrying out a first esterification reaction to obtain a first intermediate product; mixing terephthalic acid, m-phenylenediacetic acid, butanediol and a second catalyst, and carrying out a second esterification reaction to obtain a second intermediate product; performing a pre-polycondensation reaction on the first intermediate product, the second intermediate product and a pre-polycondensation catalyst in a polymerization reaction kettle to obtain a pre-polycondensation product; and carrying out final polycondensation on the pre-polycondensation product to obtain the sealing aging resistant PBAT resin. The edge sealing bag prepared from the sealing aging-resistant PBAT resin provided by the invention has more excellent sealing performance, and the sealing aging-resistant performance of the edge sealing bag is better.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of biodegradable plastics, and more specifically, to a preparation method of a sealing aging-resistant PBAT resin, biodegradable plastics and applications. Background Art

[0002] With the development of biodegradable materials, downstream applications are gradually replacing traditional non-degradable materials, especially in PE blown film products. There are two main sealing forms for blown film products, bottom sealing and side sealing. Side sealing is widely used in milk tea bags, handbags, express bags, clothing bags and other packaging fields due to its beautiful sealing edge, less bag loss and scraps, and high bag making speed. However, the current PBAT resin products have the following problems: After a certain degree of wet and hot aging or long-term storage at room temperature, the PBAT resin products made will have a decrease in sealing performance, and the sealing part will be torn in a straight line. Summary of the invention

[0003] 1. Technical issues to be resolved

[0004] The technical problem to be solved by the present invention is that the sealing performance of existing PBAT resin products decreases after a certain degree of wet-heat aging or long-term storage at room temperature, and cannot meet the use requirements.

[0005] (II) Technical solution

[0006] To achieve the above object, the technical solution adopted by the present invention is:

[0007] In a first aspect, the present invention provides a method for preparing a sealing aging resistant PBAT resin, comprising the following steps:

[0008] Adipic acid, butanediol, and a first catalyst are mixed to perform a first esterification reaction to obtain a first intermediate product, wherein the molar ratio of the adipic acid to the butanediol is in the range of (1:1.1) to (1:1.25), the molar amount of the catalyst is 0.02 to 0.04% of the molar amount of the adipic acid, the reaction temperature of the first esterification reaction is 220° C. to 230° C., and the reaction pressure is 50 to 60 KPa;

[0009] Mixing terephthalic acid, isophthalic acid, butanediol, and a second catalyst, and performing a second esterification reaction to obtain a second intermediate product, wherein the molar ratio of terephthalic acid to butanediol is (1:1.5) to (1:3), the content of isophthalic acid is 3% to 5% of the terephthalic acid, the molar amount of the second catalyst is 0.01 to 0.03% of the molar amount of the terephthalic acid, the reaction temperature of the second esterification reaction is 225°C to 235°, and the reaction pressure is 90 to 100 KPa;

[0010] The first intermediate product, the second intermediate product, and the pre-condensation catalyst are subjected to a pre-condensation reaction in a polymerization reactor to obtain a pre-condensation product, wherein the weight ratio of the first intermediate product to the second intermediate product is (1:1) to (1:2), the amount of the pre-condensation catalyst added is 0.02-0.04% of the total weight of the terephthalic acid and the adipic acid, and the reaction temperature of the pre-condensation reaction is 235°C-245°C;

[0011] The pre-polycondensation product is subjected to a final polycondensation reaction to obtain the sealing aging resistant PBAT resin, wherein the reaction temperature of the final polycondensation reaction is 230° C.-240° C.

[0012] Preferably, the pre-polycondensation product is subjected to a final polycondensation reaction to obtain the sealing aging resistant PBAT resin, which specifically comprises the following steps:

[0013] The pre-polycondensation product is slowly evacuated for 40 min to 70 min to make the vacuum degree 20 Pa to 50 Pa;

[0014] The duration of the final polycondensation reaction is 30 min-50 min. After slowly heating up, when the intrinsic viscosity of the reactant reaches a value range of 1.5 dL / g-1.7 dL / g, the final polycondensation reaction is terminated. After discharging and pelletizing in sequence, the sealing aging resistant PBAT resin is obtained.

[0015] Preferably, the first catalyst is a chelate of tetrabutyl titanate and tetraethoxysilane, the mass ratio of the tetrabutyl titanate to the tetraethoxysilane is 16:1 to 18:1, and the polycondensation catalyst is tetrabutyl titanate.

[0016] Preferably, a heat stabilizer is added during the pre-polycondensation reaction, wherein the heat stabilizer is triphenyl phosphate, and the molar amount of the heat stabilizer is 0.01-0.03% of the total molar amount of the terephthalic acid and the adipic acid.

[0017] Preferably, a cross-linking agent is added during the pre-polycondensation reaction, and the cross-linking agent is glycerol. The molar amount of the cross-linking agent ranges from 0.01 to 0.02% of the total molar amount of the terephthalic acid and the adipic acid.

[0018] Preferably, the sealing aging resistant PBAT resin has a melting point of 117-119° C., a crystallization temperature of 54-58° C., and a crystallinity of 12%-14%.

[0019] In a second aspect, the present invention also provides a thermoplastic biodegradable plastic, which comprises the following components by weight: 70-80 parts of sealing aging resistant PBAT resin, 3-5 parts of polylactic acid, 20-30 parts of calcium carbonate, 3-5 parts of talc, 0.1-0.3 parts of chain extender, 0.1-0.3 parts of internal lubricant, and 0.1-0.3 parts of external lubricant.

[0020] Preferably, the polylactic acid is Fengyuan FY-804, the chain extender is BASF epoxy chain extender ADR-4468, the internal lubricant is pentaerythritol stearate, and the external lubricant includes at least one of erucamide and PE wax.

[0021] Preferably, the calcium carbonate is calcium carbonate dispersed with stearic acid and titanate, and the particle size of the calcium carbonate is in the range of 2500-3000 mesh; the particle size of the talc is in the range of 2500-3000 mesh.

[0022] In a third aspect, the present invention further provides an application of the thermoplastic biodegradable plastic described in any one of the above technical solutions in the fields of plastic films, plastic bags and packaging materials.

[0023] (III) Beneficial effects

[0024] The above technical solution of the present invention has at least the following advantages:

[0025] 1. In the preparation method of the PBAT resin resistant to seal aging provided by the present invention, the PBAT resin resistant to seal aging is introduced into the PBAT chain. Under the same molecular weight, since the introduced isophthalic acid carries a methylene group, the proportion of the benzene ring content in the PBAT is reduced. At the same time, since the meta-position of the acetic acid group in the isophthalic acid reduces the regularity of the entire chain segment of the PBAT, the crystallinity of the PBAT copolymer is reduced, so that the PBAT has higher compatibility with other fillers such as starch, calcium carbonate, talc, etc. during downstream modification, and has better sealing performance after being made into an edge-sealed bag, and the edge-sealed bag has better sealing resistance to aging.

[0026] 2. In the present invention, in the process of preparing biodegradable plastics using the sealing aging resistant PBAT resin provided by the present invention, calcium carbonate is subjected to coupling dispersion treatment, which increases the compatibility of calcium carbonate and PBAT resin, improves the sealing effect, and also improves the sealing aging resistance of the edge-sealed bag.

[0027] 3. In the present invention, the biodegradable edge-sealed bag prepared by the biodegradable plastic provided by the present invention has excellent sealing performance. After being placed for 30 days, the sealing strength is still ≥15N / 15mm, the sealing performance loss is small, and it has excellent anti-aging performance, which can meet the use requirements of biodegradable plastic packaging bags. DETAILED DESCRIPTION

[0028] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.

[0029] In this application, "at least one" means one or more, and "plurality" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.

[0030] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "said" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.

[0031] The weight of the relevant components mentioned in the embodiment description of the present application can not only refer to the specific content of each component, but also represent the proportional relationship between the weights of the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the embodiment description of the present application, it is within the scope disclosed in the embodiment description of the present application. Specifically, the mass described in the embodiment description of the present application can be a mass unit known in the chemical industry such as μg, mg, g, kg, etc.

[0032] The terms "first" and "second" are used only for descriptive purposes to distinguish objects such as substances from each other, and should not be understood as indicating or implying relative importance or implicitly indicating the number of indicated technical features. For example, without departing from the scope of the embodiments of the present application, the first XX may also be referred to as the second XX, and similarly, the second XX may also be referred to as the first XX. Thus, features defined as "first" and "second" may explicitly or implicitly include one or more of the features.

[0033] The term “PBAT” is an abbreviation of “Poly (butylene adipate-co-terephthalate)”, which means polybutylene adipate / terephthalate.

[0034] The embodiment of the present invention provides a method for preparing a sealing aging resistant PBAT resin, comprising the following steps:

[0035] Adipic acid, butanediol, and a first catalyst are mixed to perform a first esterification reaction to obtain a first intermediate product, wherein the molar ratio of adipic acid to butanediol is in the range of (1:1.1) to (1:1.25), the molar amount of the catalyst is 0.02 to 0.04% of the molar amount of adipic acid, the reaction temperature of the first esterification reaction is 220° C. to 230° C., and the reaction pressure is 50 to 60 KPa;

[0036] Mixing terephthalic acid, isophthalic acid, butanediol, and a second catalyst, and performing a second esterification reaction to obtain a second intermediate product, wherein the molar ratio of terephthalic acid to butanediol is (1:1.5) to (1:3), the content of isophthalic acid is 3% to 5% of terephthalic acid, the molar amount of the second catalyst is 0.01 to 0.03% of the molar amount of terephthalic acid, the reaction temperature of the second esterification reaction is 225°C to 235°, and the reaction pressure is 90 to 100 KPa;

[0037] The first intermediate product, the second intermediate product, and the pre-condensation catalyst are subjected to a pre-condensation reaction in a polymerization reactor to obtain a pre-condensation product, wherein the weight ratio of the first intermediate product to the second intermediate product is (1:1) to (1:2), the amount of the pre-condensation catalyst added is 0.02-0.04% of the total weight of terephthalic acid and adipic acid, and the reaction temperature of the pre-condensation reaction is 235° C. to 245° C.;

[0038] The pre-polycondensation product is subjected to a final polycondensation reaction to obtain a sealing aging-resistant PBAT resin, wherein the reaction temperature of the final polycondensation reaction is 230° C.-240° C.

[0039] In one embodiment, the pre-polycondensation product is subjected to a final polycondensation reaction to obtain a sealing aging resistant PBAT resin, which specifically comprises the following steps:

[0040] The pre-polycondensation product is slowly evacuated for 40 min to 70 min to make the vacuum degree 20 Pa to 50 Pa;

[0041] The duration of the final polycondensation reaction is 30min-50min. After slowly heating up, when the intrinsic viscosity of the reactant reaches the range of 1.5dL / g-1.7dL / g, the final polycondensation reaction is terminated, and the material is discharged and pelletized in sequence to obtain the sealing aging resistant PBAT resin. In the process of discharging, nitrogen is filled into the polymerization reactor to increase the pressure in the polymerization reactor to 6-8kg / cm 2 .

[0042] In one embodiment, the first catalyst is a chelate of tetrabutyl titanate and tetraethoxysilane, the mass ratio of tetrabutyl titanate to tetraethoxysilane is 16:1 to 18:1, and the polycondensation catalyst is tetrabutyl titanate.

[0043] In one embodiment, a heat stabilizer is added during the pre-polycondensation reaction. The heat stabilizer is triphenyl phosphate, and the molar amount of the heat stabilizer is 0.01-0.03% of the total molar amount of terephthalic acid and adipic acid.

[0044] In one embodiment, a cross-linking agent is added during the pre-polycondensation reaction. The cross-linking agent is glycerol. The molar amount of the cross-linking agent ranges from 0.01 to 0.02% of the total molar amount of terephthalic acid and adipic acid.

[0045] In one embodiment, the sealing aging resistant PBAT resin has a melting point of 117-119° C., a crystallization temperature of 54-58° C., and a crystallinity of 12%-14%.

[0046] An embodiment of the present invention also provides a thermoplastic biodegradable plastic, which includes the following components by weight: 70-80 parts of sealing aging resistant PBAT resin, 3-5 parts of polylactic acid, 20-30 parts of calcium carbonate, 3-5 parts of talc, 0.1-0.3 parts of chain extender, 0.1-0.3 parts of internal lubricant, and 0.1-0.3 parts of external lubricant.

[0047] Specifically, the thermoplastic biodegradable plastic is prepared by the following steps:

[0048] The raw materials are weighed according to the following weight parts: 70-80 parts of the sealing aging resistant PBAT resin prepared in any of the above embodiments, 3-5 parts of polylactic acid, 20-30 parts of calcium carbonate, 3-5 parts of talc, 0.1-0.3 parts of chain extender, 0.1-0.3 parts of internal lubricant, and 0.1-0.3 parts of external lubricant. The above raw materials are stirred evenly by a high mixer and then granulated by a twin-screw extruder to obtain raw material masterbatch, wherein the extrusion temperature range of the twin-screw extruder is 150-165°C, and the screw aspect ratio is 48D.

[0049] Then the raw material masterbatch is blown into a film by a film blowing machine, wherein the processing temperature of the film blowing machine is 140-155° C. and the aspect ratio of the screw is 28-30D.

[0050] Finally, the film is processed into biodegradable edge-sealed bags by a bag-making machine, wherein the processing temperature of the bag-making machine is 200-250° C. and the bag-making speed is 110-120 bags / min.

[0051] In one embodiment, the polylactic acid is Fengyuan FY-804 (brand is Anhui Fengyuan, trademark is FY804), the chain extender is BASF epoxy chain extender ADR-4468 (brand is BASF, trademark is ADR-4468), the internal lubricant is pentaerythritol stearate, and the external lubricant includes at least one of erucamide and PE wax.

[0052] In one embodiment, the calcium carbonate is calcium carbonate dispersed with stearic acid and titanate, and the particle size of the calcium carbonate is in the range of 2500-3000 mesh; the particle size of the talc is in the range of 2500-3000 mesh.

[0053] The embodiment of the present invention also provides a use of any one of the thermoplastic biodegradable plastics in the above embodiments in the field of plastic films, plastic bags and packaging materials.

[0054] Examples 1-4

[0055] The contents of the components in the material of a biodegradable edge-sealed bag resistant to seal aging in the embodiment are shown in Table 1.

[0056] The preparation method of the biodegradable edge-sealed bag with seal aging resistance is as follows: PBAT resin with seal aging resistance, polylactic acid, calcium carbonate, talcum powder, chain extender (BASF ADR-4468), internal lubricant (pentaerythritol stearate), and external lubricant (erucic acid amide and PE wax) are weighed in a certain proportion, stirred evenly at a speed of 600r / min in a high-speed mixer, and then sent to a twin-screw extruder for granulation to obtain a raw material masterbatch. The raw material masterbatch is sent to a film blowing machine for blow molding into a film with a thickness of 55-60μm, and finally the edge is sealed on a bag making machine to make the required biodegradable edge-sealed bag with seal aging resistance.

[0057] Example 1 Example 2 Example 3 Example 4 Sealing aging resistant PBAT resin 74.04 69.04 64.04 59.04 Polylactic acid 5 5 5 5 Calcium carbonate 15 20 25 30 talcum powder 5 5 5 5 BASF ADR-4468 0.1 0.1 0.1 0.1 Pentaerythritol stearate 0.2 0.2 0.2 0.2 Erucamide 0.22 0.22 0.22 0.22 PE wax (polyethylene wax) 0.24 0.24 0.24 0.24

[0058] Table 1

[0059] Comparative Examples 1-4

[0060] The contents of the components in the material of a biodegradable edge-sealed bag in the comparative example are shown in Table 2.

[0061] The preparation method is as follows: weigh the commercially available conventional PBAT resin, polylactic acid, calcium carbonate, talc, chain extender (BASF ADR-4468), internal lubricant (pentaerythritol stearate), and external lubricant (erucic acid amide and PE wax) in a certain proportion, stir them evenly in a high-speed mixer at a speed of 600r / min, and then send them to a twin-screw extruder for granulation. Send the particles to a film blowing machine for blow molding into a film with a thickness of 55-60μm, and finally perform edge sealing treatment on a bag making machine to produce the required biodegradable edge-sealed bag.

[0062] Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Commercially available conventional PBAT resin 74.04 69.04 64.04 59.04 Polylactic acid 5 5 5 5 Calcium carbonate 15 20 25 30 talcum powder 5 5 5 5 BASF ADR-4468 0.1 0.1 0.1 0.1 Pentaerythritol stearate 0.2 0.2 0.2 0.2 Erucamide 0.22 0.22 0.22 0.22 PE wax (polyethylene wax) 0.24 0.24 0.24 0.24

[0063] Table 2

[0064] The seal strength and seal aging performance tests were performed on the biodegradable edge-sealed bags with seal aging resistance prepared in Examples 1-4 and the biodegradable edge-sealed bags prepared in Comparative Examples 1-4, and the test results are shown in Table 3. The test method is as follows: The seal strength is tested by a heat seal strength test, which is carried out in accordance with the QB / T2358 standard, and the test speed is (300±50) mm / min.

[0065]

[0066] Table 3

[0067] The test results show that the biodegradable edge-sealed bags (Examples 1-4) made of biodegradable plastic provided by the present invention still have a sealing strength of ≥15N / 15mm after being placed for 30 days. Compared with the biodegradable edge-sealed bags in the prior art (Comparative Examples 1-4), the sealing performance loss is less, the bags have excellent anti-aging properties, and can meet the use requirements of biodegradable plastic packaging bags.

[0068] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a sealing aging resistant PBAT resin, characterized in that: The following steps are involved: Adipic acid, butanediol, and a first catalyst are mixed to perform a first esterification reaction to obtain a first intermediate product, wherein the molar ratio of the adipic acid to the butanediol is in the range of (1:1.1) to (1:1.25), the molar amount of the catalyst is 0.02 to 0.04% of the molar amount of the adipic acid, the reaction temperature of the first esterification reaction is 220° C. to 230° C., and the reaction pressure is 50 to 60 KPa; Mixing terephthalic acid, isophthalic acid, butanediol, and a second catalyst, and performing a second esterification reaction to obtain a second intermediate product, wherein the molar ratio of terephthalic acid to butanediol is (1:1.5) to (1:3), the content of isophthalic acid is 3% to 5% of the terephthalic acid, the molar amount of the second catalyst is 0.01 to 0.03% of the molar amount of the terephthalic acid, the reaction temperature of the second esterification reaction is 225°C to 235°, and the reaction pressure is 90 to 100 KPa; The first intermediate product, the second intermediate product, and the pre-condensation catalyst are subjected to a pre-condensation reaction in a polymerization reactor to obtain a pre-condensation product, wherein the weight ratio of the first intermediate product to the second intermediate product is (1:1) to (1:2), the amount of the pre-condensation catalyst added is 0.02-0.04% of the total weight of the terephthalic acid and the adipic acid, and the reaction temperature of the pre-condensation reaction is 235° C.-245° C.; The pre-polycondensation product is subjected to a final polycondensation reaction to obtain the sealing aging resistant PBAT resin, wherein the reaction temperature of the final polycondensation reaction is 230° C.-240° C.

2. The method for preparing the sealing aging resistant PBAT resin according to claim 1, characterized in that: The pre-polycondensation product is subjected to a final polycondensation reaction to obtain the sealing aging resistant PBAT resin, which specifically comprises the following steps: The pre-polycondensation product is slowly evacuated for 40 min to 70 min to make the vacuum degree 20 Pa to 50 Pa; The duration of the final polycondensation reaction is 30 min-50 min. After slowly heating up, when the intrinsic viscosity of the reactant reaches a value range of 1.5 dL / g-1.7 dL / g, the final polycondensation reaction is terminated. After discharging and pelletizing in sequence, the sealing aging resistant PBAT resin is obtained.

3. The method for preparing the sealing aging resistant PBAT resin according to claim 1, characterized in that: The first catalyst is a chelate of tetrabutyl titanate and tetraethoxysilane, the mass ratio of the tetrabutyl titanate to the tetraethoxysilane is 16:1 to 18:1, and the polycondensation catalyst is tetrabutyl titanate.

4. The method for preparing the sealing aging resistant PBAT resin according to claim 1, characterized in that: A heat stabilizer needs to be added during the pre-polycondensation reaction. The heat stabilizer is triphenyl phosphate, and the molar amount of the heat stabilizer is 0.01-0.03% of the total molar amount of the terephthalic acid and the adipic acid.

5. The method for preparing the sealing aging resistant PBAT resin according to claim 1, characterized in that: A cross-linking agent needs to be added during the pre-polycondensation reaction. The cross-linking agent is glycerol. The molar amount of the cross-linking agent ranges from 0.01 to 0.02% of the total molar amount of the terephthalic acid and the adipic acid.

6. The method for preparing the sealing aging resistant PBAT resin according to claim 1, characterized in that: The sealing aging resistant PBAT resin has a melting point of 117-119° C., a crystallization temperature of 54-58° C., and a crystallinity of 12%-14%.

7. A thermoplastic biodegradable plastic, characterized in that: The components include the following in parts by weight: 70-80 parts of the sealing aging resistant PBAT resin according to any one of claims 1-6; 3-5 parts of polylactic acid; Calcium carbonate 20-30 parts; 3-5 parts of talcum powder; Chain extender 0.1-0.3 parts; Internal lubricant 0.1-0.3 parts; External lubricant 0.1-0.3 parts.

8. The thermoplastic biodegradable plastic according to claim 7, characterized in that: The polylactic acid is Fengyuan FY-804, the chain extender is BASF epoxy chain extender ADR-4468, the internal lubricant is pentaerythritol stearate, and the external lubricant includes at least one of erucamide and PE wax.

9. The thermoplastic biodegradable plastic according to claim 7, characterized in that: The calcium carbonate is calcium carbonate dispersed with stearic acid and titanate, and the particle size of the calcium carbonate is in the range of 2500-3000 meshes; the particle size of the talc is in the range of 2500-3000 meshes.

10. Use of the thermoplastic biodegradable plastic according to any one of claims 7 to 8 in the fields of plastic films, plastic bags and packaging materials.

Citation Information

Patent Citations

  • Preparation method of antistatic PBAT polymer and antistatic PBAT polymer

    CN112280018A

  • Polylactic acid-based composite material as well as preparation method and application thereof

    CN116554660A

Cited By

  • Light-aging-resistant PBAT functional resin as well as preparation method and application thereof

    CN120865526A